Mathematical Simulation Of Adaptive Allocation Of Discrete Resources; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Anisimov E. Evgeniy (2016, 2016)
Title screen